Controlling viral inflammatory lesions by rebalancing immune response patterns - Mulik, Sachin; Berber, Engin; Sehrawat, Sharvan; Rouse, Barry Tyrrell (Frontiers in Immunology, 2023)
In this review, we discuss a variety of immune modulating approaches that could be used to counteract tissue-damaging viral immunoinflammatory lesions which typify many chronic viral infections. We make the point that in several viral infections the lesions can be largely the result of one or more aspects of the host response mediating the cell and tissue damage rather than the virus itself being directly responsible. However, within the reactive inflammatory lesions along with the pro-inflammatory participants there are also other aspects of the host response that may be acting to constrain the activity of the damaging components and are contributing to resolution. This scenario should provide the prospect of rebalancing the contributions of different host responses and hence diminish or even fully control the virus-induced lesions. We identify several aspects of the host reactions that influence the pattern of immune responsiveness and describe approaches that have been used successfully, mainly in model systems, to modulate the activity of damaging participants and which has led to lesion control.We emphasize examples where such therapies are, or could be, translated for practical use in the clinic to control inflammatory lesions caused by viral infections.